Contemporary Indian Writing in English - Mehrotra Charu (Ed.) (New Delhi Atlantic, 2019)
A quick glimpse of the views and ideas of Vikram Seth, Anuradha Marwah, Arun Joshi, Aravind Adiga, Chetan Bhagat, Kiran Desai, A.K. Ramanujan, Kamala Das, Mahesh Dattani, Jhumpa Lahiri, Arundhati Roy, V.S. Naipaul, Sharan Kumar, and Shobha De. With the critical in sights and information provided by the various authors in this rich collection of articles.
Keywords: Essays; Indian English Literature; English Literature